URINARY STONE DENSITY MEASURED ON NON-CONTRAST COMPUTED TOMOGRAPHY CORRELATED WITH SUCCESS RATE BY EXTRACORPOREAL SHOCKWAVE LITHOTRIPSY TREATMENT - Chalcheska, Slavica; Stojovska-Jovanovska, Elizabeta; Stojanoski, Ivica; Kostadinovski, Vlatko; Panev, Sandra Dejanova; Prgova, Biljana Veljanovska (Journal of Morphological Sciences, 2021)
Measurements of urinary calculi density in Hounsfield Unit, stone size, site by non-contrast computed tomography (NCCT), correlated with success rate by extracorporeal shock wave lithotripsy (ESWL) outcome in complete fragmentation, fragments less than 5 mm or incomplete fragmentation. Retrospective study comprising 40 patients with urinary calculus of 10-20 mm divided into two groups (10-15 mm and 16-20 mm), with defining stone location, site and attenuation measured in Hounsfield Unit (HU), divided into three groups:1- Soft stones <6500HU; 2- Medium stones 650-1200HU; 3- Hard stones >1200HU. All treated from 4000-4500 shock waves. Success in initial stone disintegration was defined with a plain film X-ray in 5-6 weeks. Completely disintegrated calculus was confirmed in 31 (77.5%), up to 5 mm fragments in 3 (7.5%) and unsuccessful in 6 (15.0%) patients. The percentage difference between complete disintegration versus up to 5 mm fragments or failed disintegration  was extremely statistically significant for p<0.05 (Difference test, p=0.001). High percentage calculated after one treatment in 2- Medium stone group 650-1200HU in 15 (60%) patients, in 6 (24%) of the 1-Soft stone group, and in 3-Hard stone group in 4 (16%).Percentage difference between the 2-Medium stone group after one ESWL treatment versus the 1-Soft stone group and 3-Hard stone group was statistically significant for p<0.05 (Difference test, p=0. 0162). Study findings show that the attenuation value of stones can predict successful outcome of ESWL treatment for the upper urinary tract, and it has a greater impact on ESWL outcome than the stone size and site. Keywords: non-contrast computed tomography (NCCT), Hounsfield Unit (HU), extracorporeal shockwave lithotripsy (ESWL), disintegration, attenuation. https://doi.org/10.55302/JMS2141054ch